Milling the Mistletoe: Nanotechnological Conversion of African Mistletoe (Loranthus micranthus) Intoantimicrobial Materials - Muhammad Sarfraz; Sharoon Griffin; Tamara Gabour Sad; Rama Alhasan; Muhammad Jawad Nasim; Muhammad Irfan Masood; Karl Herbert Schäfer; Chukwunonso E.C.C. Ejike; Cornelia M. Keck; Claus Jacob; Azubuike P. Ebokaiwe (MDPI AG, 2018)
Nanosizing represents a straight forward technique to unlock the biological activity of complex plant materials. The aim of this study was to develop herbal nanoparticles with medicinal value from dried leaves and stems of Loranthus micranthus with the aid of ball-milling, high speed stirring, and high-pressure homogenization techniques. The milled nanoparticles were characterized using laser diffraction analysis, photon correlation spectroscopy analysis, and light microscopy. The average size of leaf nanoparticles was around 245 nm and that of stem nanoparticles was around 180 nm. The nanoparticles were tested for their antimicrobial and nematicidal properties against a Gram-negative bacterium Escherichia coli, a Gram-positive bacterium Staphylococcus carnosus, fungi Candida albicans and Saccharomyces cerevisiae, and a nematode Steinernemafeltiae. The results show significant activities for both leaf and (particularly) stem nanoparticles of Loranthus micranthus on all organisms tested, even at a particle concentration as low as 0.01% (w/w). The results observed indicate that nanoparticles (especially of the stem) of Loranthus micranthus could serve as novel antimicrobial agents with wide-ranging biomedical applications.